2010
DOI: 10.1177/1098611110373997
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Emotional Labor and Value Dissonance on Burnout Among Police Officers

Abstract: Burnout among police officers is a well-documented phenomenon, with police exhibiting significantly rates significantly higher than other occupations. This is not surprising considering the inherent dangers and challenges police face in the course of their duties. However, police are also subject to a host of institutional and cultural forces that are likely to contribute to burnout. This study examines the variety of ways self-processes, societal and institutional policing values, and demands for emotional pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
131
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(143 citation statements)
references
References 55 publications
6
131
2
4
Order By: Relevance
“…Supporting this idea, previously we found that in response to these same conversations, officers reported feeling more negative and less positive emotion when experiencing greater job stress (Roberts & Levenson, 2001). Our present findings therefore offer some behavioral evidence to support notions that officers do manage emotions in their personal as well as professional lives (Brown & Grover, ; Schaible & Gecas, ).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Supporting this idea, previously we found that in response to these same conversations, officers reported feeling more negative and less positive emotion when experiencing greater job stress (Roberts & Levenson, 2001). Our present findings therefore offer some behavioral evidence to support notions that officers do manage emotions in their personal as well as professional lives (Brown & Grover, ; Schaible & Gecas, ).…”
Section: Discussionsupporting
confidence: 77%
“…Law enforcement is physically and emotionally exhausting (Maslach & Jackson, ; Senjo & Dhungana, ). It requires “emotion management”—suppressing personal feelings and expressing emotions not actually felt—even among fellow officers (Pogrebin & Poole, , ; Schaible & Gecas, ; Tracy, ). Similarly, officers may hide their true feelings at home.…”
mentioning
confidence: 99%
“…Stress, feelings of inauthenticity, and decreased job satisfaction arise because the officers experience emotional dissonance or a misalignment of their true feelings with respect to their display of emotions. Negative outcomes are more likely to occur during deep acting than during surface acting because the feelings of emotional dissonance are believed to be much stronger in deep acting (Grandey, 2003;Schaible & Gecas, 2010). Understanding the negative outcomes of emotional labor is important because the results from this study suggest that female officers are more likely to use caring or feelings as a strategy of interaction, whereas male officers are more likely to use behavior.…”
Section: Performance and Emotional Labormentioning
confidence: 84%
“…A second study of Dutch police officers (Taris et al, 2010) found that higher job demand and lower feelings of professional efficacy lead to higher emotional exhaustion. In their sample of US police officers, Schaible and Gecas (2010) surprisingly found that surface acting was not related to emotional exhaustion.…”
Section: Relationships Of Health and Job Satisfaction To Exhaustionmentioning
confidence: 94%